Design analysis and performance enhancement of a 2-element MIMO skin-implantable antenna for IoT-based health monitoring devices. - Anupma Gupta; Mohammad Aljaidi; Shonak Bansal; Rabia Emhamed Al Mamlook; Vipan Kumar; Abeer Aljohani; Saad Aljohani; Manish Kumar Singla (PLoS ONE)
Two two-element slotted patch multiple-input multiple-output (MIMO) antenna with coplanar waveguide (CPW) feed is proposed for deployment in implantable medical devices. Implantable devices are compact and demand high-gain antennae with unidirectional radiation patterns. Regarding compactness, the antenna has a size of 16 × 6×0.25 mm3 for the operating frequency of 2.45 GHz ISM band. Miniaturized antenna geometry is attained using the slots in the radiator and with the coplanar waveguide feed. An element MIMO configuration is used for establishing a reliable communication link. The two radiators maintain a connected ground topology with a minimum edge-to-edge spacing of 7.7 mm. Mutual coupling of -29 dB and operating frequency spectrum of 1300 MHz is attained at the center cut off frequency. Unidirectional power pattern and high gain of 2.3 dB is achieved. The proposed MIMO structure is suitable for mitigating multipath fading effect and realizing higher spectral efficiency in short range communication. The in-tissue measurement results for the scattering parameters and radiation characteristics are done by placing the antenna in a pork loin. Specific absorption rate (SAR) analysis is performed to confirm the user's safety from nearfield EM waves. Antenna has safe SAR value of 0.798 W/kg for 1-g of average tissue for the power of 1-mW. The low envelope correlation coefficient of 0.035 depicts the excellent diversity performance for MIMO operation.